Psychological Well-Being para Siswa Sekolah Menengah Atas - Nardani, Novita Eko; Khusumadewi, Arie; Winingsih, Evi (Universitas Sebelas Maret, 2025)
High school students are experiencing a transitional period from adolescence into early adulthood, making them increasingly in need of support to enhance their psychological well-being. Psychological well-being is essential because it enables them to handle developmental pressures, strengthen academic and social competencies, and maintain emotional and mental stability. This study employs a literature review approach to gather and examine relevant findings from previously published works. Based on the literature reviewed, it can be inferred that psychological well-being is a fundamental element in fostering the growth of high school students. When psychological well-being is at an optimal level, students become more capable of managing academic, social, and emotional demands, while also developing stronger self-identity, emotional regulation, learning motivation, and preparedness for making career decisions. Internal personal factors, such as self-efficacy, resilience, mindfulness, gratitude, interest in learning, and hardiness, substantially influence the formation of psychological well-being. Furthermore, external and spiritual influences, including religiosity and social support, also contribute meaningfully by strengthening students’ sense of meaning in life and supporting their emotional balance.